2006
DOI: 10.1016/j.aquaculture.2006.03.011
|View full text |Cite
|
Sign up to set email alerts
|

Microsatellite–centromere mapping in the Japanese eel (Anguilla japonica) by half-tetrad analysis using induced triploid families

Abstract: Genetic improvement of the Japanese eel (Anguilla japonica) can be achieved by artificially controlling its life cycle using recent advances in reproductive biology. In this study, we developed 43 microsatellite loci to confirm Mendelian inheritance at 10 5 of them as well at 16 previous reported in two full-sib families produced by artificial insemination. In order to establish a base for aquaculture genetics of this species in the near future, these microsatellite loci were mapped in relation to the centrome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
24
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 26 publications
3
24
0
Order By: Relevance
“…However out of 804 female heterogametic SNP loci, 395 loci (49.12%) showed heterozygote frequencies above 0.67, indicative of crossover interference in seabass chromosomes. This phenomenon is well documented in the literature for other fish species [4, 8, 43, 55]. Similar proportion of markers (48.1%) with heterozygosity exceeding 0.67 were observed in turbot ( Scophthalmus maximus ) [56].…”
Section: Discussionsupporting
confidence: 79%
“…However out of 804 female heterogametic SNP loci, 395 loci (49.12%) showed heterozygote frequencies above 0.67, indicative of crossover interference in seabass chromosomes. This phenomenon is well documented in the literature for other fish species [4, 8, 43, 55]. Similar proportion of markers (48.1%) with heterozygosity exceeding 0.67 were observed in turbot ( Scophthalmus maximus ) [56].…”
Section: Discussionsupporting
confidence: 79%
“…Unreduced gamete production can also often be induced or enhanced by environmental stimuli (Ramsey and Schemske 1998;Mason et al 2011b;De Storme et al 2012). Half-tetrad analysis has been carried out in a number of animal species to map centromeres: zebrafish (Johnson et al 1995), cape honeybee (Baudry et al 2004), abalone (Nie et al 2012), Japanese eel (Nomura et al 2006), oyster (Hubert et al 2009), carp (Liu et al 2013), turbot flatfish (Martinez et al 2008), and sea cucumber (Nie et al 2011). Plant species centromeres have been genetically mapped using half-tetrad analysis in maize (Schneerman et al 1998;Lin et al 2001), alfalfa (Tavoletti et al 1996), mandarin (Cuenca et al 2011;Aleza et al 2015), and potato .…”
mentioning
confidence: 99%
“…Although the observed heterozygosity at Veva08 was 0.000 in gynogenetic population (0.565 in cultivated population), the observed heterozygosity at other locus was higher (0.250-0.944) in gynogenetic population owing to higher recombination rate. High recombination rates have also been reported in many fish species, such as Japanese eel Anguilla japonica (Temminck & Schlegel) (recombination rate, y = 0.645) (Nomura et al 2006), large yellow croaker Pseudosciaena crocea (Richardson) (y = 0.586) (Li et al 2008). Conversely, Zheng et al (2007) found that the average values of H O were zero in both meio-gynogenesis-1 group and meiogynogenesis-2 group of grass carp when the average values of H O were 0.1181 in Xiangjiang river group.…”
Section: Discussionmentioning
confidence: 91%